EXPRESSION AND FUNCTIONAL INTERACTION OF CHICKEN RbAp46 POLYPEPTIDE WITH HISTONES, HISTONE DEACETYLASE-1, AND HISTONE ACETYLTRANSFERASE-1 - Ahyar Ahmad; Harningsih Karim (Indonesian Journal of Chemistry, 2013)
In this study, we cloned and sequenced cDNA encoding the chicken p46 polypeptide, RbAp46. The cDNA encoding a protein consists of 424 amino acids is a member of the WD protein family, with seven WD repeat motifs, and exhibits 90.3% identity to RbAp48, and 94.3% identity to the human RbAp46. The RbAp46 fusion protein were synthesized by in vitro translation system and in Escherichia coli under induction by 50 µM IPTG and single step purified with glutathione-Agarose beads, showed that GST-tagged protein of approximately 72 kDa. The in vitro experiment established that RbAp46 interacts with chicken histones, chHDAC-1, and chHAT-1. The in vitro immunoprecipitation experiment, involving truncated mutants of RbAp46, revealed not only that two regions comprising amino acids 33-179 and 375-404 are necessary for its binding to H2B, but also that two regions comprising amino acids 1-32 and 405-424 are necessary for its binding to H4. Furthermore, the GST pulldown affinity assay, involving truncated mutants of RbAp46, revealed that a region comprising amino acids 359-404 binds to chHAT-1 in vitro. Taken together, these results indicate not only that RbAp46 should participate differentially in a number of DNA-utilizing processes through interactions of its distinct regions with histones and chHAT-1, but also that the proper propeller structure of RbAp46 is not necessary for its interaction with chHAT-1.